2012
DOI: 10.1021/ja3054354
|View full text |Cite
|
Sign up to set email alerts
|

Curved Polycyclic Aromatic Molecules That Are π-Isoelectronic to Hexabenzocoronene

Abstract: Reported here are two types of curved π-molecules that are π-isoelectronic to planar hexabenzocoronene (HBC) but are forced out of planarity either by an embedded seven-membered ring or by atom crowding at the fjord region. Embedding a heptagon in HBC leads to a novel saddle-shaped molecule 1, whose π-backbone is slightly less curved than the previously reported [7]circulene in terms of the average Gauss curvature, but surprisingly much more rigid than [7]circulene. Overcrowded fjord regions in novel derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
165
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(170 citation statements)
references
References 44 publications
3
165
0
2
Order By: Relevance
“…1,7 However, these interesting carbon nanostructures with negative curvature remain imaginary, and heptagonembedded polycyclic arenes that can serve as segments, model compounds, and in principle, synthetic precursors for them are still rare. Recent approaches to negatively curved carbon nanostructures with saddle-shaped polycyclic arenes 8 include a heptagon-embedded peri-hexabenzocoronene (HBC) 9 and C 80 H 30 , a grossly warped nanographene containing five heptagons. 10 Here we report derivatives of C 70 H 26 (1a,b) and C 70 H 30 (2a,b), two new saddle-shaped polycyclic arenes containing two heptagons as shown in Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7 However, these interesting carbon nanostructures with negative curvature remain imaginary, and heptagonembedded polycyclic arenes that can serve as segments, model compounds, and in principle, synthetic precursors for them are still rare. Recent approaches to negatively curved carbon nanostructures with saddle-shaped polycyclic arenes 8 include a heptagon-embedded peri-hexabenzocoronene (HBC) 9 and C 80 H 30 , a grossly warped nanographene containing five heptagons. 10 Here we report derivatives of C 70 H 26 (1a,b) and C 70 H 30 (2a,b), two new saddle-shaped polycyclic arenes containing two heptagons as shown in Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The positions of the four alkoxy groups were important to activate the cyclization at the desired position as noted earlier with the synthesis of the heptagonembedded HBC. 9 The propyl groups of 3c were then replaced with other alkyl chains yielding 3a,b. The propyl group was chosen as the solubilizing substituent in this synthesis because it not only provided reasonable solubility to 3c for convenient purification but also, upon dealkylation with BBr 3 , resulted in 1-bromoproane, which was easily removed under reduced pressure before the subsequence alkylation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Goddard et al [20] synthesised nearly pure hexabenzocoronene and benzodicoronene crystal samples from pyrene. Unlike usual planar hexabenzocoronene, a novel saddle-shaped molecule was synthesised by embedding a seven-membered ring [30]. The difficulty in the preparation of the bulk system highlights the advantage of computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Heptagon-embedded hexaperi-benzocoronene (HBC) 7 was synthesized from 10 using FeCl3 as both Lewis acid and oxidant for the Scholl-type cyclodehydrogenation reaction. [13] It was found that the position of alkoxyl groups plays a key role in this reaction. It is necessary to equip the heptagon-containing hexaphenylbenzene with alkoxyl groups ortho or para to the reaction sites since the Scholl-type reaction is reported to form C-C bonds preferably ortho or para to activating substituents.…”
Section: O M M E N T a R Y T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%